Social media marketing amongst millennial’s in Malaysia: issues and challenges - Roza Husin, Wann Huzida; Harun, Amran (UTHM, 2019)
Social Media Marketing (SMM) is an internet marketing strategy with an emphasis on using social networking sites like Facebook, Twitter and Instagram to earn potential customers to visits the website. Social media marketing are very important nowadays to help people stay connected with others and gain information. Therefore it is very imperative to further understand how Millennials whom are the highest internet user respond to social media marketing. This study will review the literature pertaining to social media marketing within the millennial scope. Additionally, this study will explore the issues and challenges of social media marketing in Malaysia. The implication of the study is social media marketing consist of two newly dimensions namely entertainment and perceived trust and this dimensions are important on this study.